Tat Twam Asi and Derrida’s Differance for a Greener Accounting - Putu Yudha Asteria Putri (Yayasan Rumah Peneleh, 2021)
This article aims to present a cultural accounting research methodology that is local as well as religious to construct a greener accounting. Construction methodology employed was substantive interrelationships between Jacques Derrida's thought of “differance” and an alternative path called Tat Twam Asi as the teachings of chastity without limits. The meaning contained in the teachings of Tat Twam Asi is